Contamination, exposure and risk assessment of mercury in the soils of an artisanal gold mining community in Ghana. (March 2021) - Gyamfi, Opoku; Sørensen, Peter Borgen; Darko, Godfred; Ansah, Eugene; Vorkamp, Katrin; Bak, Jesper Leth
Abstract: Mercury pollution has pervaded many artisanal gold mining communities in the world, especially in developing countries. This study aimed to evaluate the potential risk of mercury pollution in soils in Gbani, an artisanal gold mining community in Ghana. Two hundred and thirty-seven soil samples were collected from within 0–10 cm depth, from active mining sites near residences, two transects in the community, waste soil from mining processing and the surroundings of the community. The measured mean mercury soil concentrations were 71 mg Hg/kg in active mining sites, and more moderate (2.7 mg Hg/kg) along transects through the community. Enrichment Factors classified the soils of the study area as being moderately to extremely severely contaminated with mercury. The spatial distribution shows the contamination of mercury is highest at residential facilities and decreases through the community to the outskirts covered by vegetation. Hazard quotients for non-cancer effects identified air-borne exposure pathways for humans to pose the largest risk, including the inhalation of vapour. The average hazard indices recorded were 0.5 (child) and 0.1 (adult) at the grid, 2 (child) and 0.3 (adult) at the transects, 1.6 (child) and 0.2 (adult) for waste soil and 76 (child) and 10.9 (adult) at the mining sites. The inhabitants of Gbani community are therefore at risk of non-cancer effects of mercury as the hazard quotients and hazard index were above one. Highlights: Soil mercury concentration high in mining sites near residential facilities and decreases through community to outskirts. Mean concentration at the mining sites exceeds most regulatory limits for mercury in soil Soils classified as moderately-to extremely severely-contaminated with mercury and that contamination is not uniform Mercury levels measured pose non-cancer health risk to people living in the community Children are at a higher risk than adults and the risk is elevated at mining sites than the outskirts.